Perspectives of the Metabolic Engineering of Terpenoid Indole Alkaloids in Catharanthus roseus Hairy Roots - Zhao, L.; Sander, G.W.; Shanks, J.V.
This review looks back on how the terpenoid indole alkaloid pathway and the regulatory factors in Catharanthus roseus were identified and characterized, and how metabolic engineering, including genetic engineering and metabolic profiling, was conducted based on the gained knowledge. In addition, further examination of the terpenoid indole alkaloid pathway is proposed.
Keywords: CATHARANTHUS ROSEUS; GENETIC ENGINEERING; METABOLIC ENGINEERING; METABOLIC PROFILING; TERPENOID INDOLE ALKALOIDS